Motifs of Three HLA-DQ Amino Acid Residues (α44, β57, β135) Capture Full Association With the Risk of Type 1 Diabetes in DQ2 and DQ8 Children - Zhao, Lue Ping; Papadopoulos, George K.; Kwok, William W.; Moustakas, Antonis K.; Bondinas, George P.; Larsson, Helena Elding; Ludvigsson, Johnny; Marcus, Claude; Samuelsson, Ulf; Wang, Ruihan; Pyo, Chul-Woo; Nelson, Wyatt C.; et al. (Diabetes (New York, N.Y.), 2020)
HLA-DQA1 and -DQB1 are strongly associated with type 1 diabetes (T1D), and DQ8.1 and DQ2.5 are major risk haplotypes. Next-generation targeted sequencing of HLA-DQA1 and -DQB1 in Swedish newly diagnosed 1- to 18 year-old patients (n = 962) and control subjects (n = 636) was used to construct abbreviated DQ haplotypes, converted into amino acid (AA) residues, and assessed for their associations with T1D. A hierarchically organized haplotype (HOH) association analysis allowed 45 unique DQ haplotypes to be categorized into seven clusters. The DQ8/9 cluster included two DQ8.1 risk and the DQ9 resistant haplotypes, and the DQ2 cluster included the DQ2.5 risk and DQ2.2 resistant haplotypes. Within each cluster, HOH found residues α44Q (odds ratio [OR] 3.29, P = 2.38 * 10−85) and β57A (OR 3.44, P = 3.80 * 10−84) to be associated with T1D in the DQ8/9 cluster representing all ten residues (α22, α23, α44, α49, α51, α53, α54, α73, α184, β57) due to complete linkage disequilibrium (LD) of α44 with eight such residues. Within the DQ2 cluster and due to LD, HOH analysis found α44C and β135D to share the risk for T1D (OR 2.10, P = 1.96 * 10−20). The motif “QAD” of α44, β57, and β135 captured the T1D risk association of DQ8.1 (OR 3.44, P = 3.80 * 10−84), and the corresponding motif “CAD” captured the risk association of DQ2.5 (OR 2.10, P = 1.96 * 10−20). Two risk associations were related to GAD65 autoantibody (GADA) and IA-2 autoantibody (IA-2A) but in opposite directions. CAD was positively associated with GADA (OR 1.56, P = 6.35 * 10−8) but negatively with IA-2A (OR 0.59, P = 6.55 * 10−11). QAD was negatively associated with GADA (OR 0.88; P = 3.70 * 10−3) but positively with IA-2A (OR 1.64; P = 2.40 * 10−14), despite a single difference at α44. The residues are found in and around anchor pockets 1 and 9, as potential T-cell receptor contacts, in the areas for CD4 binding and putative homodimer formation. The identification of three HLA-DQ AAs (α44, β57, β135) conferring T1D risk should sharpen functional and translational studies.